PENGARUH PENDIDIKAN KESEHATAN DENGAN LAYANAN PESAN SINGKAT WHATSAPP TERHADAP PENGETAHUAN DAN SIKAP REMAJA MENGENAI KEHAMILAN TIDAK DIINGINKAN DI SMAN 1 KUBU - Ni Luh Putu Anik Cahyani; Meril Valentine Manangkot; Ida Arimurti Sanjiwani (Coping: Community of Publishing in Nursing, 2021)
Unwanted pregnancy is one of the major health issues for teenagers. This could happen because of lack of knowledge and actions to prevent unwanted pregnancies. One of the efforts to prevent unwanted pregnancy is by providing health education by using WhatsApp. This study aimed to determine the effect of health education with WhatsApp text service about unwanted pregnancies to the teenagers’ knowledge and attitude. The research was held on 21 April-6 May 2019. This research was quasi-experimental research with pretest and posttest and control group design. Respondents consisted of 54 students that obtained by simple random sampling technique. Intervention on this study was done to by sending a text message to the WA group twice a day for two weeks. The knowledge was measured by unwanted pregnancy knowledge instrument and attitude was measured with Brief Sexual Attitude Scale. Data analyzed was used Mann Whitney test. This research showed there was difference in knowledge (p=0,024, p<0,05) and there was no difference in attitude (p=0,444, p>0,05). Based on this result, it expected that health workers could be using WhatsApp to provide health education, especially about reproductive health.